Emissão de CO2 do solo em áreas de floresta plantada no Cerrado do Mato Grosso do Sul - Vicentini, Maria Elisa [UNESP] (2017)
The increase in CO2 concentration in the Earth's atmosphere was the main cause of global warming, accounting for about 60% of total greenhouse gas emissions. The objective of this work was to characterize the temporal patterns of CO2 emission, temperature, humidity and soil O2 capture, as well as their relationships in areas of Eucalyptus, Pinus and Ciliary forest reforested in a dystrophic Red Latosol in the Biome Cerrado, in the region of the municipality of Selvíria - MS. The study was conducted in three reforested areas located in the municipality of Selvíria-MS. Experimental areas consisted of forests planted with eucalyptus (EU), riparian forest (MA), pinus (PI). The CO2 emission from the soil was recorded using the LI-COR system (LI-8100) and the determination of soil O2 a uptake by means of the UV Flux 25% system. The results of CO2 emission, temperature, humidity and O2 capture were evaluated by means of repeated measures in time, by means of mixed models and descriptive statistics. Tukey's test was performed at a 5% probability level. The ratio of emitted CO2 to O2 consumed (RQ) was calculated. The mean CO2 emission of the soil in the studied areas EU, MA, PI, was 5.61; 5.53 and 4.06. μmol m-2 s-1 respectively. EO2 did not differ statistically in the three areas studied. MA had the highest soil moisture value. Most of the RQ values were <1. The total CO2 emissions recorded in 193 days of evaluation were 11.26 Mg ha-1 for EU 10.99 Mg ha-1, MA and 7,97 Mg ha-1 PI, which differed significantly (p <0, 05). Rainfall and soil moisture influenced the variations of soil CO2 emissions. Pinus forest soils emit less CO2.